Hybrid dilute sulfuric acid and aqueous ammonia pretreatment for improving butanol production from corn stover with reduced wastewater generation. (April 2019) - Xiao, Min; Wang, Lan; Wu, Youduo; Cheng, Chi; Chen, Lijie; Chen, Hongzhang; Xue, Chuang
Graphical abstract: Highlights: An efficient hybrid DA-AA pretreatment method was established. Sugar yield and butanol production were improved by optimizing washing times. Wastewater generation was reduced by making fine use of two-step neutralization. Abstract: An efficient hybrid pretreatment method was developed for butanol production from corn stover using dilute sulfuric acid (DA) and aqueous ammonia (AA). With the optimized AA concentration, treatment temperature and time of 10% AA, 80 °C and 24 h, the hybrid pretreatment could effectively dissolve hemicellulose and lignin with solid recovery rate of 37.45% and lignin reduction rate of 86.77% compared to those of 57.75% and 45.84% from single DA pretreatment. By washing 1 time after each step treatment, sugar yield and butanol production were increased to 401.76 mg/g-CS and 10.89 g/L from 346.04 mg/g-CS and 9.33 g/L obtained without washing. Compared with conventional single DA and AA pretreatment methods, wastewater generation was reduced to 0.83 L/g-butanol from 2.11 and 3.46 L/g-butanol, indicating this hybrid pretreatment could be an effective approach for improving butanol production from lignocellulosic feedstocks.